The role of perfusion effects in monitoring of chemoradiotherapy of rectal carcinoma using diffusion-weighted imaging - Ganten, Maria-Katharina; Schüßler, Maximilian; Bäuerle, Tobias; Münter, Marc; Schlemmer, Heinz-Peter; Jensen, Alexandra; Brand, Karsten; Dueck, Margret; Dinkel, Julien; Kopp-Schneider, Annette; Maier-Hein, Klaus H.; Stieltjes, Bram (Cancer imaging, 2013)
Purpose: The aim of this study was to characterize and understand the therapy-induced changes in diffusion parameters in rectal carcinoma under chemoradiotherapy (CRT). The current literature shows conflicting results in this regard. We applied the intravoxel incoherent motion model, which allows for the differentiation between diffusion (D) and perfusion (f) effects, to further elucidate potential underlying causes for these divergent reports. Materials and methods: Eighteen patients with primary rectal carcinoma undergoing preoperative CRT were examined before, during, and after neoadjuvant CRT using diffusion-weighted imaging. Using the intravoxel incoherent motion approach, f and D were extracted and compared with postoperative tumor downstaging and volume. Results: Initial diffusion-derived parameters were within a narrow range (D1 = 0.94 ± 0.12 × 10−3 mm2/s). At follow-up, D rose significantly (D2 = 1.18 ± 0.13 × 10−3 mm2/s; P < 0.0001) and continued to increase significantly after CRT (D3 = 1.24 ± 0.14 × 10−3 mm2/s; P < 0.0001). The perfusion fraction f did not change significantly (f1 = 9.4 ± 2.0%, f2 = 9.4 ± 1.7%, f3 = 9.5 ± 2.7%). Mean volume (V) decreased significantly (V1 = 16,992 ± 13,083 mm3; V2 = 12,793 ± 8317 mm3, V3 = 9718 ± 6154 mm3). T-downstaging (10:18 patients) showed no significant correlation with diffusion-derived parameters. Conclusions: Conflicting results in the literature considering apparent diffusion coefficient (ADC) changes in rectal carcinoma under CRT for patients showing T-downstaging are unlikely to be due to perfusion effects. Our data support the view that under effective therapy, an increase in D/ADC can be observed.
Gesehen am 03.03.2020